LEGAL VALIDITY OF A LAND DEED EXECUTED BY A LAND DEED OFFICIAL WITHOUT BEING READ BEFORE THE PARTIES - Yenni Kartika; Rasji Rasji (Awang Long Law Review, 2026)
The Deed of the Land Deed Official plays an essential role in guaranteeing legal certainty over the transfer of land rights. However, in practice, violations of formal requirements often occur, such as the failure to read the deed before the parties. This study aims to analyze the validity of a deed of grant that was not read in the presence of the parties, as well as the legal liability of the Land Deed Official for executing a deed that does not comply with the prescribed procedures. This research employs a normative juridical method with a statutory approach and a case study analysis of Decision Number 298/Pdt.G/2021/PN Kpg. The results of the study indicate that a Land Deed Official’s deed that is not read before the parties constitutes a deed with a formal defect, causing it to lose its status as an authentic deed and, consequently, depriving it of full legal evidentiary strength. In addition, a Land Deed Official who neglects the obligation to read the deed may be held legally liable administratively, civilly, as well as ethically under professional conduct standards. In conclusion, the reading of the deed before the parties is not merely a procedural formality, but rather constitutes a form of legal protection and a moral responsibility of the Land Deed Official to ensure validity and fairness in every legal act concerning land affairs.